Effect of aluminium on hydrogen permeation of high-manganese twinning-induced plasticity steel. (1st April 2015) - Han, D.K.; Lee, S.K.; Noh, S.J.; Kim, S.-K.; Suh, D.-W.
Abstract : To investigate the hydrogen mobility in high-manganese twinning-induced plasticity (TWIP) steels, high-temperature permeation tests were conducted. They showed that the addition of aluminium to TWIP steel decreases the permeability and diffusivity of hydrogen and increases the solubility, which implies that one of the effects of aluminium in suppressing the hydrogen-induced mechanical degradation comes from a reduction in hydrogen mobility. The findings on diffusivity and solubility are consistent with an earlier calculation that considered aluminium–hydrogen interactions.